C1222C Deletion in Exon 8 of ABL1 Is Involved in Carcinogenesis and Cell Cycle Control of Colorectal Cancer Through IRS1/PI3K/Akt Pathway - Liu, Yi; Cao, Jian; Zhu, Ya-Ning; Ma, Yu; Murtaza, Ghulam; Li, Yu; Wang, Jian-Hua; Pu, Yan-Song (Frontiers in Oncology, 2020)
Colorectal cancer (CRC) is one of the most commonly diagnosed cancers worldwide. ABL1 (c-Abl) is a non-receptor tyrosine kinase, whose role and molecular mechanism in CRC remain largely unclear. The aim of this study was to elucidate the role of ABL1 to obtain information on colon cancer gene mutation. We analyzed the tissue samples obtained from patients with CRC, CRC cell lines, and the immunodeficient mice. The proliferation, cell cycle, and apoptosis of CRC cells were examined. IPA software was used to analyze the molecules involved in CRC after ABL1 RNA interference. We found ABL1 was highly expressed in CRC tissues and cells. This high expression was associated with the TNM stage of CRC patients. In exon 8 of the ABL1 gene, we identified a novel mutation of C1222C deletion, which was related to the CRC stage. Depletion of ABL1 resulted in the inhibition of proliferation and escalation of apoptosis in two CRC cell lines, SW480 and HCT-116. Our in vivo study also demonstrated that depletion of ABL1 reduced CRC tumor progression. The results of the ingenuity pathway analysis indicated that the expression of 732 genes was upregulated and that of 691 genes was downregulated in mice transplanted with ABL1-downregulated CRC cells, among which we confirmed that depletion of ABL1 inhibited TGF-β1 via IRS1/PI3K/AKT pathway in CRC progression. These findings demonstrated that ABL1 plays an important role and that it can be a potential molecular target for CRC therapy.